Teachers' preference for later school start times. (19th December 2021) - Albrecht, Joëlle N.; Werner, Helene; Yaw, Mei Ling; Jenni, Oskar G.; Huber, Reto
Summary: Early morning school start times conflict with biologically determined sleep phase preference and thus contribute to common sleep deficits. This conflict is most pronounced in adolescents, and numerous studies have confirmed that later school start times are beneficial for their sleep and health. However, the conflict continues to exist beyond adolescence and, accordingly, also teachers might benefit from later school start times, but this has gained little attention so far. Importantly, teachers' resistance to delay school start time is one of the key barriers for a successful implementation and, therefore, teachers' school start time preferences and influencing factors are important to consider. To this end, we conducted an online survey. Teachers ( n = 694, 56.1% female) from 17 high schools in Zurich, Switzerland, participated in the study. They indicated their school start time preference. In addition, four predictor blocks were assessed: sociodemographic, school‐/work‐related, and sleep characteristics, as well as teachers' perception of students in the first morning lesson. Mixed models were applied to predict the preference. The majority (51%) endorsed later school start times (median preferred delay 25.2 min). School start time, sleep characteristics and perception of students in the first morning lesson were significant predictors for the preference. Thus, teachers with more misaligned sleep and higher awareness for students' issues in the early morning were more likely to report a preference. This suggests psychoeducation about sleep biology throughout life span to be an effective measure to increase teachers' support to delay school start time, especially because also they themselves are likely to benefit from later school start times.